2014
DOI: 10.1155/2014/658679
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatment on Residual Stress in Cold-Forged Parts

Abstract: Residual stresses are those stresses that remain in a body when there is no external load applied. Numerous factors can induce residual stresses in the material, including cold forming. Thermal treatments of steel are widely used because they can improve the mechanical properties of the steel, such as toughness, tenacity, and resistance; however, thermal treatments can also produce residual stresses. This study aims to analyze the residual stresses present in a cold-forged part after heat treatments. Half-cyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The cold rolling and subsequent annealing of Invar alloys result in the recovery and recrystallization of the alloys. The rearrangement and annihilation of dislocations during recovery and grain nucleation and growth during recrystallization can drastically alter not only the mechanical properties of alloys, but also the residual stress [15][16][17]. It is known that the underlying factors that contributes to changes in the mechanical properties of a material can readily affect the residual stress of the material.…”
Section: Introductionmentioning
confidence: 99%
“…The cold rolling and subsequent annealing of Invar alloys result in the recovery and recrystallization of the alloys. The rearrangement and annihilation of dislocations during recovery and grain nucleation and growth during recrystallization can drastically alter not only the mechanical properties of alloys, but also the residual stress [15][16][17]. It is known that the underlying factors that contributes to changes in the mechanical properties of a material can readily affect the residual stress of the material.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that most researchers reduce the residual stress of forgings by adjusting the heat treatment process parameters. However, as far as the present technology is concerned, it is impossible to completely eliminate the residual stress of forgings by heat treatment [15]. In addition, it was found that the qualified rate of a certain type of blade is increased by 20%-30% after heat treatment and the adjustment of cutting process parameters, but there are still a lot of scrapped products due to deformation, and the total qualified rate is only 70%.…”
Section: Introductionmentioning
confidence: 99%
“…The residual stress is concentrated in the region defects causing easier destruction around the vacancy [5]. The residual stresses are dependent on the factors including heat treatment applied, in addition to the intensity and nature of the residual stresses originally within the body [6]. Scanning contact potentiometry (SCP) is a new non-destructive material testing method making it possible to assess the microstructure of the object material without affecting or damaging it.…”
Section: Introductionmentioning
confidence: 99%